Importance of estimation of follicular output rate (FORT) in females assisted by intracytoplasmic sperm injection - Rehman, Rehana; Mustafa, Rozina; Hoor, Talea; Khan, Rakhshaan; Gul, Hina (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2017)
Background: We aimed to estimate pregnancy outcome after ICSI in terms of oocyte parameters, embryo quality, endometrial thickness, hormone and cytokine levels in women stratified on the basis of follicular output rate (FORT). Methods: Quasi experimental design was carried out after approval from “Ethical review board of Islamabad clinic serving infertile couples” from July 2010 to August 2013. One thousand and fifty females were selected with the criteria of age between 21-40 years, infertility of more than 2 years, body mass index of 18-35 kg/m2, menstrual cycle of 25 ± 7 days, both ovaries present with normal uterine cavity, serum FSH levels less than 8 IU/ml and normal thyroid-stimulating hormone levels. Females on short agonist or antagonist protocol with diagnosis of polycystic ovarian syndrome, fibroids or in their male partner sperms retrieved by testicular biopsy were excluded from the study. Down regulation of ovaries was followed by controlled ovarian stimulation, Ovulation Induction (OI), oocyte pick up, in vitro fertilization, Embryo Transfer (ET) and confirmation of pregnancy was done by serum beta hCG of more than 25 mIU/ml and cardiac activity on trans vaginal scan. Enzyme linked immuno sorbent assay was used for peak and mid luteal estradiol (E2), progesterone (P) and interleukin I-β estimation on OI and ET days respectively. FORT (ratio of preovulatory follicle count to antral follicle count × 100 on OI day) stratified females into low under the 33rd percentile, medium between the 33rd and the 67th percentile and high above the 67th percentile. Characteristics of groups were compared by one way analysis of variance. Results: Females 276 (33%), 288 (34%) and 282 (33%) comprised of low, medium and high FORT groups respectively. The number of retrieved, mature and fertilized oocytes, cleaved embryos, endometrial thickness and number of gestational sacs in the high FORT group was significantly high (P <0.001). High peak and midluteal E2 (P = 0.0025, 0.0001), low P (P = 0.0001) and high peak interleukin-1β (P = 0.0001) was observed in high FORT in comparison with medium FORT with resultant greater number of clinical pregnancies 183 (65%). Conclusions: The FORT in non PCOS patients may reflect good reproductive outcome after ICSI with maximum clinical pregnancies in high FORT group.